The Influence of Transformational Leadership Style of Traditional Leaders in The Prevention of Teenage Premarital Pregnancy - Riyanti, Riyanti; Agus Salim, Lutfi; Nurmala, Ira; Basuki Notobroto, Hari; Hartini, Nurul (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Teenage premarital pregnancy is a population issue that requires preventive efforts involving various parties, including traditional leaders as part of the community around adolescents. This study aimed to determine the influence of transformational leadership style on the role of traditional leaders in preventing teenage premarital pregnancy. This observational study used a cross-sectional design involving 200 traditional leaders selected through a simple random sampling technique. The independent variables were transformational leadership style and sociodemographic factors, while the dependent variable was the role of traditional leaders in preventing teenage premarital pregnancy. Data were collected using a questionnaire and analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis with multiple logistic regression. The results showed that sociodemographic factors (age, gender, education, occupation, and income) did not significantly influence the role of traditional leaders (p>0.05). However, work experience had a significant effect (OR=0.514, p=0.023). Transformational leadership style also had a significant influence (OR=15.910, p=0.001). Multivariate analysis revealed that transformational leadership style was the most influential factor on the role of traditional leaders (OR=17.127, 95% CI=8.093–36.246, p<0.001). It can be concluded that transformational leadership style plays a crucial role in strengthening the role of traditional leaders in preventing teenage premarital pregnancy. Transformational leadership training programs for traditional leaders are strongly recommended, and collaboration between government and health institutions with traditional leaders in adolescent reproductive health programs should be enhanced.